Evaluation of the Implementation of Motorized Vehicle Tax Payments Through Samsat Bunda at UPT Madiun Regional Revenue Management - Hestina Arinda, Devia (Universitas Airlangga, 2023)
Abstract The complexity of the bureaucracy of motorized vehicle tax payment services in the view of ordinary people is the main attraction of this research. Real-time services to taxpayers continue to be carried out by the Regional Revenue Agency of East Java Province, where technically, local tax collection is carried out by the Regional Revenue Management Technical Implementation Unit and the Joint One-Stop Administrative System Office (Samsat). The Samsat Bunda service results from a collaboration between the Regional Revenue Agency and State-Owned Enterprises, and the private sector with Village-Owned Enterprises to facilitate the payment of motor vehicle tax for taxpayers in villages. This research aims to achieve the successful implementation of Samsat Bunda in the work area of UPT Madiun Regional Revenue Management as a non-cash way of paying motorized vehicle taxes with unlimited service time and space. The research method used is descriptive qualitative, explaining the research data carried out by observation, in-depth interviews, and documentation. The results of the study show that the Samsat Bunda implementation has been done well and can be a solution for people far from the reach of conventional Madiun Samsat services. On the other hand, the results of the revenue realization from the collection of motorized vehicle tax through Samsat Bunda are still relatively small. However, there is progress in increasing the completion of revenue from tax assessment letters and the nominal rupiah paid. Apart from that, Samsat Bunda is not a priority and the leading choice for village communities as taxpayers in carrying out their tax-abiding obligations. Keywords: policy evaluation, motor vehicle tax, samsat bunda Abstrak Rumitnya birokrasi pelayanan pembayaran Pajak Kendaraan Bermotor dalam pandangan masyarakat awam menjadi daya tarik pada penelitian ini. Pelayanan secara real-time kepada wajib pajak terus dilakukan oleh Badan Pendapatan Daerah Provinsi Jawa Timur yang secara teknis pemungutan pajak daerahnya dilaksanakan oleh Unit Pelaksana Teknis Pengelolaan Pendapatan Daerah dan Kantor Bersama Sistem Administrasi Manunggal Satu Atap (Samsat). Layanan Samsat Bunda merupakan hasil kerjasama antara Badan Pendapatan Daerah dan Badan Usaha Milik Negara dan/atau sektor swasta dengan Badan Usaha Milik Desa untuk memudahkan pembayaran pajak kendaraan bermotor bagi wajib pajak yang berada di desa-desa. Penelitian ini bertujuan pencapaian keberhasilan pelaksanaan samsat bunda pada wilayah kerja UPT Pengelolaan Pendapatan Daerah Madiun sebagai cara pembayaran pajak kendaraan bermotor secara non tunai dengan pelayanan tidak terbatas waktu pelayanan dan ruang. Metode penelitian yang digunakan adalah kualitatif deskriptif yang akan menjelaskan data-data penelitian yang dilakukan dengan observasi, wawancara mendalam dan dokumentasi. Hasil penelitian menunjukkan bahwa pelaksanaan Samsat Bunda sudah dilaksanakan dengan baik dan dapat menjadi solusi bagi masyarakat yang jauh dari jangkauan pelayanan konvensional Samsat Madiun. Di sisi lain, hasil realisasi penerimaan atas pemungutan pajak kendaraan bermotor melalui samsat bunda masih relatif kecil walaupun terdapat progress kenaikan realisasi penerimaan dari surat ketetapan pajak dan nominal rupiah yang dibayarkan. Selain itu, Samsat Bunda juga belum menjadi prioritas dan pilihan utama bagi masyarakat desa selaku wajib pajak dalam menjalankan kewajiban taat pajak. Kata kunci: evaluasi kebijakan, pajak kendaraan bermotor, samsat bunda.